PENGARUH SOLVABILITAS DAN NILAI PASAR TERHADAP HARGA SAHAM PERUSAHAAN (Saektor Trade, Service & Investment yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2016-2020) - Muhamad Ahpas, - (2022)
This study aims to determine and analyze the effect of Solvency as measured by Debt to Equity Ratio (DER) and Market as measured by Earning Per Share (EPS) on stock prices as measured by the annual closing price of listed trading, service and investment sector companies. on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. This research uses descriptive and verification methods. The data used in this study are secondary data sourced from statistical reports and company financial reports. The research population is 180 companies in the trade, services and investment sectors listed on the Indonesia Stock Exchange for the 2016-2020 period. The samples taken were 96 companies, using purposive sampling technique. The analysis technique used is (1) panel data analysis based on the test model consisting of the Chow test, Haussman test and Lagrange multiplier test. And the last analysis technique is (2) Hypothesis Testing through Regression Significance Test (F Test) and Regression Coefficient Significance Test (t Test). Prior to panel data analysis, the Classical Assumption Test was performed using the Linearity Test, Multicollinearity Test, Autocorrelation Test and Heteroscedasticity Test as a requirement to be able to perform panel data regression tests. In this study, data processing uses Eviews 9 software. Based on the results of the F test in this study, it shows that Solvency and Market Value have an effect on stock prices. Based on the t test, the results of this study indicate that solvency has a negative effect on stock prices and market value has a positive effect on stock prices. As for the value of the Adjusted R-squared of 0.868699 or 86.87%. Keywords: Stock Price, Solvency, Debt To Equity Ratio (DER), Market Value, Earning Per Shares (EPS), Signaling Theory.